FACULTY PERCEPTIONS AND OBJECTIVE IMPACT OF FACULTY DEVELOPMENT WORKSHOPS: Impact of Faculty Development Workshops - Hashim, Rizwan; Qamar, Khadija; Ali, Salman; Khan, Viqar Ahmed (Pakistan Armed Forces Medical Journal, 2014)
Objective: To document the perception of participants and the impact of faculty development and related educational workshops arranged in a public sector medical education setting.Place and Duration of Study: The departments of Medical Education (DME); Army Medical College and Armed Forces Post Graduate Medical Institute, Rawalpindi, Pakistan from 2013 to 2014.Study Design: A descriptive study.Subject and Methods: During 2013 to 2014, nine faculty educational workshops were arranged by the faculty members of the departments of Medical Education (DME), Army Medical College and Armed Forces Post Graduate Medical Institute, Rawalpindi, Pakistan. Both clinical and pre-clinical teaching faculty members attended the workshops. Proper consent was taken from each participant to document their perceptions for this study.Results: Two hundred and forty of the teaching faculty members of the Army Medical Corps participated in different proportion for the workshop arranged during a period of one year. At the end of each workshop a questionnaire was completed by each participant. The study addressed the perceptions of the participants regarding impact of workshop, the facilitator’s knowledge about the workshop topic and his/her communication skills. The responses of the participants were documented for each question and the percentages were calculated.Conclusion: The planning efforts of professional development workshops by the departments of medical education at Army Medical College and Armed Forces Postgraduate Medical Institute resulted in a satisfactory implementation of the set objectives for faculty development.